Artists' Books 1983. - Guest, Tim; Nakahara, Yusuke (Tokyo : Gallery Lunami, 1983)
Baldessari, John ; Bartolini, Luciano ; Becher, Bernd & Hilla ; Boogaerts, Pierre ; Broodthaers, Marcel ; Brouwn, Stanley ; Carrion, Uliese ; Clemente, Francesco ; Darboven, Hanne ; Feldmann, Hans-Peter ; Fulton, Hamish ; LeWitt, Sol ; Luthi, Urs ; Maciunas, George ; Mers, Mario ; Nannucci, Maurizio ; Nauman, Bruce ; Ontani, Luigi ; Paolini, Giulio ; Parmiggiani, Claudio ; Penck, A.R. ; Rot, Dieter ; Ruscha, Ed ; Snow, Michael ; Hagiwara, Sakumi ; Kashihara, Etsutomu ; Kishida, Nagako ; Matsuzawa, Yutaka ; Moriya, Yukiyoshi ; Nakahara, Yusuke ; Takamatsu, Jiro ; Nakayama, Masaki ; Niikuni, Siichi ; Yamazaki, Naohide
Artists' Books 1983, Gallery Lunami, Tokyo, May 23-28 1983
English-Japanese
kunstcatalogus